Technology Skills in the Workplace: Information Professionals' Current Use and Future Aspirations. - Maceli, Monica; Burke, John J. (Information Technology & Libraries, 2016)
Information technology serves as an essential tool for today's information professional, and ongoing research is needed to assess the technological directions of the field over time. This paper presents the results of a survey of the technologies used by library and information science practitioners, with attention to the combinations of technologies employed and the technology skills that practitioners wish to learn. The most common technologies employed were email, office productivity tools, web browsers, library catalog- and database-searching tools, and printers, with programming topping the list of most-desired technology skill to learn. Similar technology usage patterns were observed for early and later-career practitioners. Findings also suggested the relative rarity of emerging technologies, such as the makerspace, in current practice.